Safety and Efficacy of Bimekizumab in Patients with Psoriatic Arthritis: 2-Year Results from Two Phase 3 Studies - Philip J. Mease; Joseph F. Merola; Yoshiya Tanaka; Laure Gossec; Iain B. McInnes; Christopher T. Ritchlin; Robert B. M. Landewé; Akihiko Asahina; Barbara Ink; Andrea Heinrichs; Rajan Bajracharya; Vishvesh Shende; et al. (Rheumatology and Therapy)
Abstract Introduction Psoriatic arthritis (PsA) is a chronic inflammatory disease requiring long-term treatment. Bimekizumab, a monoclonal IgG1 antibody that selectively inhibits interleukin (IL)-17F in addition to IL-17A, has demonstrated tolerability and sustained clinical efficacy for up to 1 year for patients with PsA. Here, we report the longer-‍term safety and efficacy of bimekizumab up to 2 years. Methods BE OPTIMAL (biologic disease-modifying antirheumatic drug [bDMARD]-naïve) and BE COMPLETE (prior inadequate response/intolerance to tumor necrosis factor inhibitors [TNFi-IR]) assessed subcutaneous bimekizumab 160 mg every 4 weeks in patients with PsA. BE OPTIMAL included a reference arm (adalimumab 40 mg every 2 weeks); patients switched to bimekizumab at week 52 with no washout between treatments. BE OPTIMAL week 52 and BE COMPLETE week 16 completers were eligible for the BE VITAL open-label extension. Efficacy outcomes are reported to week 104/100 (BE OPTIMAL/BE COMPLETE). Results A total of 710/852 (83.3%) bDMARD-naïve and 322/400 (80.5%) TNFi-IR patients completed week 104/100. Up to 104 weeks, patients treated with bimekizumab in BE OPTIMAL and BE COMPLETE had treatment-emergent adverse event incidence rates (exposure-adjusted incidence rate/100 patient-years) of 179.9 (95% CI 166.9, 193.7) and 100.3 (89.2, ‍112.4), respectively. The proportion of patients achieving efficacy outcomes (≥ 50% improvement from baseline in American College of Rheumatology [ACR] response criteria, 100% improvement from baseline in Psorisis Area and Severity Index [PASI], minimal disease activity [MDA]) was sustained in all patients from week 52 to week 104/100. Conclusions Bimekizumab was well tolerated for up to 2 years of treatment and no new safety signals were observed. Sustained clinical efficacy was observed up to 2 years in bDMARD-naïve and TNFi-IR patients with active PsA. Patients switching from adalimumab to bimekizumab demonstrated further improvement in skin and nail symptoms, and sustained efficacy in joint symptoms. Trial Registration BE OPTIMAL (NCT03895203), BE COMPLETE (NCT03896581), BE VITAL (NCT04009499).